Pagkapit Sa Hangin - So, Joshua Lim (Likhaan: The Journal of Contemporary Philippine Literature; Vol 18 No 1 (2024): LIKHAAN 18 The Journal of Contemporary Philippine Literature, 2024)
August 2021. COVID-19 delta wave overwhelms the only hospital in an unnamed island. The health workers have been working nonstop for over twenty-four hours. Then the delivery of oxygen tanks does not arrive. In the Temporary Treatment and Monitoring Facility (TTMF) of the public hospital, the doctor and two staff nurses decide to lower the oxygen levels of those whom they believe are going to die soon, in effect hastening these patients’ deaths. But their desperate attempt to save oxygen is found out by a watcher—a relative assigned to take care of their patient—who refuses to accept that nothing more can be done to save her father’s life.